2015
DOI: 10.1210/en.2015-1227
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Placental Responses in Fetal Development

Abstract: The placenta is an ephemeral but critical organ for the survival of all eutherian mammals and marsupials. It is the primary messenger system between the mother and fetus, where communicational signals, nutrients, waste, gases, and extrinsic factors are exchanged. Although the placenta may buffer the fetus from various environmental insults, placental dysfunction might also contribute to detrimental developmental origins of adult health and disease effects. The placenta of one sex over the other might possess g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
247
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(257 citation statements)
references
References 146 publications
10
247
0
Order By: Relevance
“…Finally, if germ cells are exposed to toxic metals and/or endocrine disruptors and undergo epigenomic reprogramming, multi-and transgenerational effects may be noted following prenatal exposure in the F1. Effects of prenatal exposure to endocrine disruptors & toxic metals on the fetal epigenome Review mental differences between placentas derived from male or female fetuses may result in sexually dimorphic responses to environmental exposures [132]. It has recently been shown that gene-specific methylation differs between male and female placentas and these genes are enriched for immune function, transport of substances across the placenta, and transcription factors [133].…”
Section: Review Bommarito Martin and Frymentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, if germ cells are exposed to toxic metals and/or endocrine disruptors and undergo epigenomic reprogramming, multi-and transgenerational effects may be noted following prenatal exposure in the F1. Effects of prenatal exposure to endocrine disruptors & toxic metals on the fetal epigenome Review mental differences between placentas derived from male or female fetuses may result in sexually dimorphic responses to environmental exposures [132]. It has recently been shown that gene-specific methylation differs between male and female placentas and these genes are enriched for immune function, transport of substances across the placenta, and transcription factors [133].…”
Section: Review Bommarito Martin and Frymentioning
confidence: 99%
“…Specifically, male placentas have enriched expression of genes related to inflammation and immune functioning, while female placentas have enriched expression of immune-regulating genes [134,135]. These immunologic differences between male and female fetuses may result in greater vulnerability in male fetuses when faced with adverse environmental exposures in utero [132]. Additionally, differences in the expression of glucocorticoid receptors have been observed based on fetal sex, which may result in differential fetal susceptibility to the maternal stress and/or immune response following exposure to environmental contaminants [136,137].…”
Section: Review Bommarito Martin and Frymentioning
confidence: 99%
“…In support of this hypothesis, physiologic differences between male and female placentas have been observed [19]. For example, placentas derived from pregnancies of males and females display variation in the abundance and type of glucocorticoid transporter proteins, the expression of hormones and the production of immune-related proteins including cytokines [12,[19][20][21]. In addition, sex-based differences in response to prenatal stressors have been observed at the levels of the placental proteome, transcriptome and epigenome [3,7,14,20,[22][23][24][25][26][27].…”
mentioning
confidence: 93%
“…We hypothesize that sex-dependent health outcomes in infants may be associated with sexual dimorphism of the placenta. In support of this hypothesis, physiologic differences between male and female placentas have been observed [19]. For example, placentas derived from pregnancies of males and females display variation in the abundance and type of glucocorticoid transporter proteins, the expression of hormones and the production of immune-related proteins including cytokines [12,[19][20][21].…”
mentioning
confidence: 96%
“…Alternatively, upregulation or maintenance of labyrinth growth may aid in maintaining nutrient transfer to help ensure fetal survival. Changes to the labyrinthine vasculature are also likely to contribute to the observed sex specific alterations in gene expression of glucose and nutrient transporters, glucocorticoid responsive genes, growth factors, as well as inflammatory responses, see reviews by Clifton (2010) and Rosenfeld (2015). Further research into sexual dimorphism of labyrinthine differentiation, vasculogenesis and branching morphogenesis, interhemal membrane thickness, and functional nutrient transport assays may shed light on sex differences in placental efficiency and adaptation to maternal perturbations.…”
Section: Sexually Dimorphic Programming Of the Labyrinthmentioning
confidence: 99%